A Gothic Counter-narrative of the Italian Civil War: Landolfi's Racconto d'autunno. (10th November 2020) - Roccella, Paola
Abstract : Tommaso Landolfi's Racconto d'autunno (1947) has often been interpreted by scholars as a (peculiar) Resistance narrative. However, although the novella proceeds from a historical situation, one typical of Resistance novels, it suddenly becomes an undefinable kind of Gothic tale that questions the notion of "liberation" and sheds light on some of the Liberation's more controversial episodes. Specifically, Landolfi recounts a traumatic episode from the final phase of the war that, at the time, had not yet entered official accounts: the mass rapes and killings that followed the Battle of Monte Cassino (May-June 1944). I argue that Racconto d'autunno employs Gothic fiction and its deceptive strategies to convey the feeling of displacement induced by traumatic war events. The interplay between the natural and supernatural powerfully illustrates the destabilization of the civilian population caused by the war. I demonstrate this by comparing passages from the novella with victims' oral testimonies of the war, collected by the historian Tommaso Baris. Finally, this article challenges readings of Landolfi's fiction as predominantly ironic and playful and encourages a deeper historical and cultural contextualization of his works, one that highlights their complex relations to the reality they are immersed in.